UPM Corporate Video: English. - Universiti Putra Malaysia, Bahagian Komunikasi Korporat (Universiti Putra Malaysia, 2014)
This video shows the history of changes in Universiti Putra Malaysia, which started from the Sekolah Pertanian Malaya in 1931, and then upgraded to the Kolej Pertanian Malaya in 1947, and later developed into the Universiti Pertanian Malaysia in 1971, and subsequently changed its name to Universiti Putra Malaysia in 1997, in line with development in various fields of studies. This video also shows the facilities available at the university to support the learning, teaching and research in accordance with the status of UPM as a Research University in Malaysia.